2020
DOI: 10.1155/2020/1973241
|View full text |Cite
|
Sign up to set email alerts
|

EGFRPolymorphism and Survival of NSCLC Patients Treated with TKIs: A Systematic Review and Meta-Analysis

Abstract: Tyrosine kinase inhibitor- (TKI-) based therapy revolutionized the overall survival and the quality of life in non-small-cell lung cancer (NSCLC) patients that have epidermal growth factor receptor (EGFR) mutations. However, EGFR is a highly polymorphic and mutation-prone gene, with over 1200 single nucleotide polymorphisms (SNPs). Since the role of EFGR polymorphism on the treatment outcome is still a matter of debate, this research analyzed the available literature data, according to the PRISMA guidelines fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 75 publications
0
33
0
1
Order By: Relevance
“…EGFR/HER1 is a member of the epidermal growth factor receptor (EGFR) family and plays important roles in development and tumorigenesis, e.g. lung tumors [13 , 14] . HER receptors are often overexpressed or mutated in many tumors and thus are considered as important targets for anti-tumor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…EGFR/HER1 is a member of the epidermal growth factor receptor (EGFR) family and plays important roles in development and tumorigenesis, e.g. lung tumors [13 , 14] . HER receptors are often overexpressed or mutated in many tumors and thus are considered as important targets for anti-tumor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous subsets of tumor with different molecular targets may lead to different resistance levels to cancer therapy and the progression of final clinical outcomes [5 , 6] . This is mainly due to the presence of heterogeneity of EGFR polymorphisms (variation) and clinical response, and EGFR variations has a better therapy outcome [7 , 8] .…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of these studies involved small groups of patients. In a very recent meta-analysis, Jurisic et al [ 33 ] summarized the results in NSCLC, showing that rs712829 significantly affected OS and PFS in patients receiving gefitinib or erlotinib. In turn, the largest study among lung cancer patients given RT and standard CHT was carried out in a Chinese population; however, the authors found no relationship between the SNPs we examined and prognosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on the predictive and prognostic potential of EGFR SNPs has mainly focused on EGFR-directed therapy with small-molecule tyrosine kinase inhibitors (TKIs) and anti-EGFR monoclonal antibodies (mAbs). Although the results of these studies are not conclusive, some of them show an association between EGFR SNPs and the efficacy of EGFR–targeted treatment in lung cancer as well as in other solid tumors [ 29 , 30 , 31 , 32 , 33 ]. However, very little is known about their possible influence on the effects of RT or CHT with platinum drugs commonly used in NSCLC treatment.…”
Section: Introductionmentioning
confidence: 99%